THE ROLE OF INFORMATION CULTURE IN THE UNIVERSITY KNOWLEDGE MANAGEMENT SYSTEM - Lomachinska, Irina; Lomachinskyi, Bohdan (Educological discourse, 2021)
The article is devoted to the role of information culture in ensuring the effectiveness of knowledge management at the university. Based on the ideas of P. Drucker and I. Nonaka on the need for continuous self-education of the individual using professional collective experience in the process of practical training, means of improving the efficiency of knowledge management are considered, in particular, introduction of innovative leadership models, research activity expansion, creation of conditions for improving the system of advanced training, the formation of an electronic knowledge base as a reflection of the collective intellectual potential and labor market analytics with the subsequent involvement of advanced ideas to improve the professional competencies of graduates. In the knowledge management at the university, information culture performs a number of important functions: educational, ideological, communicative, technological, the function of preserving social memory. Proposed approaches to the analysis of information culture are: information (as a body of knowledge, skills and abilities to effectively meet information needs), communicative (the required level of communication competence), culturological (providing a holistic vision of the world based on the values of its spiritual development), technological (skills and abilities to work in the IT-sphere), methodological (methods of operating information arrays), management (effective management of information resources). The conclusions emphasize that the information culture at the university is formed by cognitive and epistemic expectations anticipated in the implementation of tasks and decision-making. The information culture of the university is based on organizational values, leadership, norms and conduct regarding the exchange and use of information, and the possibility of digital rethinking of knowledge management is largely determined by a clear organizational strategy aimed at innovation. Measures aimed at improving the level of students’ information culture mobilize analytical approaches in the evaluation of information, improve the quality of work with information resources and network systems, contribute to the generation of knowledge and their practical use in future professional experience.